ROLE OF FINE NEEDLE ASPIRATION CYTOLOGY AS “ONE STOP” DIAGNOSIS FOR ASSESSMENT OF BREAST LUMPS IN WOMEN: Life Sciences-Pathology - KUMAR HARSH; BUCH ARCHANA C; PAL SUKANYA; CHANDANWALE SHIRISH S; JOSHI ROHAN V (International Journal of Life Science and Pharma Research, 2022)
Breast lumps in women are a common clinical problem that requires rapid and accurate diagnosis with an important aim of excluding any malignancy. Careful evaluation, exact diagnosis and definite treatment are mandatory for managing breast lumps. This study was conducted to evaluate the efficacy of fine needle aspiration cytology (FNAC) for diagnosis of breast lumps in women. 100 patients were evaluated by FNAC from July 2012 to September 2014 and results were compared with histopathology. Sensitivity, specificity, positive and negative predictive value and accuracy were calculated. Out of 100 patients (n=100), 65% were diagnosed as benign disease by FNAC and 35% as malignant. On histopathology 2 cases turned out to be false negative. FNAC showed a sensitivity of 94.59% and specificity of 100% with a positive predictive value of 100%, negative predictive value of 96.2% and accuracy rate of 98%. FNAC showed 100% diagnostic accuracy for malignancy. It helps to minimize delay in diagnosis. It reduces anxiety in patients and avoids unnecessary open biopsy. FNAC plays an important role to provide a “one stop” diagnosis for assessment of breast lumps in women.